Antisocial personality disorder and therapeutic pessimism – how can mentalization-based treatment contribute to an increased therapeutic optimism among health professionals? - Flaaten, Emilie; Langfeldt, Maria; Morken, Katharina T. E. (Frontiers in Psychology, 2024)
Antisocial personality disorder (ASPD) is associated with therapeutic pessimism among health professionals. Several variables are associated with obstacles in therapist’s willingness to treat ASPD. Variables that are relevant are (i) confusion associated with the term ASPD, (ii) characteristics of the disorder, (iii) attitudes, experiences, and knowledge clinicians possess, and (iv) insufficient management of countertransference. We assume that therapeutic pessimism is related to the lack of evidence-based, effective treatment for individuals with ASPD. This is problematic because ASPD is associated with large socio-economic costs and considerable suffering for the individual and the society. Mentalization-based treatment (MBT) was developed in treating borderline personality disorder (BPD) and is now considered an effective treatment for this group. Mentalization is defined as the process by which individuals make sense of themselves and others in terms of subjective states and mental processes. This ability affects an individual’s psychological functioning, mental health, self-organization, and interpersonal relationships. The overall goal of MBT is to strengthen the individual’s mentalizing abilities and facilitate more adaptive handling of problematic, internal states. Recently, a version of MBT tailored for individuals with ASPD (MBT-ASPD) has been developed. The purpose of this review is to investigate how MBT-ASPD relates to the major obstacles that contribute to the therapeutic pessimism toward this group. Despite a limited evidence base, preliminary studies indicate promising results for MBT-ASPD. More research is still required, this review suggests MBT-ASPD can contribute to increased therapeutic optimism and demonstrate specific characteristics of MBT-ASPD that contribute to management of therapeutic pessimism.